IĞDIR CARPET PILLOWS WITH REGIONAL PROPERTIES - Yusuf ÇETİN (Fırat University, 2019)
One of the most common weaving art of the Iğdır region, which is very rich in traditional hand weavings, is carpet pillows. Every color and motif used in the Iğdır region carpet pillows has a language and meaning. On one hand, these carpet pillows exhibit a rich repertoire of adornment; on the other hand, the motifs handled have been used for centuries as a means of nonverbal communication. These motifs, which are composed as a result of stylization of plants, animals and various objects, have been conveyed up to this day from generation to generation. However, the change of the past traditional lifestyle seen in the region and the arrangement of home furnishing in accordance with the modern times have led to the decrease of carpet pillow weavings. Very few examples of these traditional handicraft products that are not weaved much any more have survived until today. As it is located in a traditional region the Iğdır carpet pillows bear the traces of Azerbaijan, Iran and Anatolia and they attract attention with their compositinal qualities and richness in motifs. While the wool used in carpet pillows were dyed with madder, in recent examples also chemical dyes have been used and the natural colors of wools have been utilized too. As a general aspect of the weavings in the region in the Iğdır carpet pillows have a very hard weaving technique which is called ‘, ’ the Turkish Knot’’ , this is woof knotting method. It is necessary to preserve and convey the future generations these precions national heritage handicraft products whose production decreases day by day andthe surviving samples of which have been eroded.